2009
DOI: 10.1371/journal.pone.0005485
|View full text |Cite
|
Sign up to set email alerts
|

Diurnally Entrained Anticipatory Behavior in Archaea

Abstract: By sensing changes in one or few environmental factors biological systems can anticipate future changes in multiple factors over a wide range of time scales (daily to seasonal). This anticipatory behavior is important to the fitness of diverse species, and in context of the diurnal cycle it is overall typical of eukaryotes and some photoautotrophic bacteria but is yet to be observed in archaea. Here, we report the first observation of light-dark (LD)-entrained diurnal oscillatory transcription in up to 12% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 53 publications
1
60
0
Order By: Relevance
“…The multiple lines of evidence discussed above indicate that the KaiC family is likely a major hub of a versatile and complex archaeal signaling network that so far has largely escaped attention. Nevertheless, the available experimental data on a halobacterial circadian clock (24,57) and the recent progress in the study of the functions of FlaH in the archaellum (35,36,45) allow us to propose two models of the roles of KaiC-like proteins in signal transduction (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple lines of evidence discussed above indicate that the KaiC family is likely a major hub of a versatile and complex archaeal signaling network that so far has largely escaped attention. Nevertheless, the available experimental data on a halobacterial circadian clock (24,57) and the recent progress in the study of the functions of FlaH in the archaellum (35,36,45) allow us to propose two models of the roles of KaiC-like proteins in signal transduction (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Among archaea, diurnal gene expression has been demonstrated only in Halobacteria (24,57,60). It has been shown that KaiC-like proteins undergo cyclic expression, and deletion of most of them affected the expression of the others, suggesting that Halobacteria indeed might have a bona fide KaiC-based circadian mechanism (38).…”
Section: Resultsmentioning
confidence: 99%
“…Disproving this notion, Huang et al (1990) demonstrated that the phototrophic marine cyanobacterium Synechococcus elongatus displays a robust circadian rhythm. More recently, it was shown that photoheterotrophic Halobacterium synchronize their physiologies with a light-dark cycle (Whitehead et al, 2009). Evidence of this diel behavior has been found in individual organisms throughout the microbial world, pointing to its critical role in the ecology and evolution of microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the expression of ϳ12% of genes from the halophilic archaeon Halobacterium salinarum NRC-1 has been found to oscillate with either ultradian (13-h) or circadian (22-h) periodicity under constant conditions after 3 days of entrainment in an LD cycle (98). The halophilic archaeon Haloferax volcanii harbors 4 cryptic kaiC-like genes, cirA, cirB, cirC, and cirD, that share 28% to 33% identity with and 48% to 55% similarity to KaiC from S. elongatus and possess predicted Walker A and B motifs (99).…”
Section: Archaeal Rhythmsmentioning
confidence: 99%